First Geographical Record of Corymorpha bigelowi (Cnidaria: Hydrozoa, Corymorphidae) in the Northern Red Sea Coast of Egypt, Based on Morphological Description - Fedekar, Fadel Madkour; Walaa, Safwat Zaghloul; Samya, Hussein Mohammad (International Marine Science Journal, 2019)
The Anthomedusae species, Corymorpha bigelowi Maas, 1905 (Cnidaria: Hydrozoa, Corymorphidae), was recorded in the northern Red Sea fauna, representing it "first invasion" in Egypt. A fact proven by past studies that this species is endemic in the Indo-Pacific region, which is mainly located in southern coast of Japan and Indian Ocean. The specimens were collected from an area located off Hurghada city, and between latitudes 27° 14.427ˊ and 27° 10.816ˊ N, and longitudes 33° 51.085ˊ and 33° 51.603ˊ E using plankton net (350 µm mesh). In total, six mature medausae of C. bigelowi were caught in December 2014 and February 2015 (4 and 2 medusae, respectively). Following this, the captured species medusa of C. bigelowi was photographed and morphological characteristics described in details. As well as, further discussions of biogeographical distribution and morphological speciation of the present species were provided. This work makes a noteworthy contribution to clarify the migration route of C. bigelowi from southern Red Sea to the Mediterranean Sea. nih.gov/pmc/articles/PMC3155160/
Keywords: Hydromedusae; Corymorpha bigelowi; Red Sea; biogeographic distribution; gelatinous zooplankton